Modeling and rational determination of the main biomechanical characteristics in javelin throwing. - Adashevskiy V.M.; Dylewski Michal; Iermakov S.S. (Fizičeskoe Vospitanie Studentov, 2011)
The possibilities of the use of biomechanical models in training athletes. The approaches in the construction of biomechanical models. A biomechanical model of throwing the javelin. An solution to the problem of dynamic influence on flight range spear absolute initial rate of departure, departure angle, height of release of the spear. The most important biomechanical characteristics of the "athlete-spear. " The possibilities of using individual features of the athlete to achieve better results.